2012
DOI: 10.1007/s11033-012-2105-y
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 polymorphisms and breast cancer risk

Abstract: Breast cancer (BC) is one of the most common causes of death among women, and second in Iran. The objectives of this study were to determine the frequency of RAD51 G/C polymorphism in patients with breast cancer. We evaluated these polymorphisms and effects on the breast cancer risk association in a Iranian sporadic population-based case-control study of 294 breast cancer cases and 315 controls using a PCR-RFLP-based assay. Analyses of affected and controls show that homozygote genotype RAD51 GG has the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Different meta-analysis and studies on RAD51 have earlier shown an association of this polymorphism with an elevated breast cancer risk (Cole et al, 2011;Falvo et al, 2011;Gao et al, 2011;Hosseini et al, 2012). The RAD51 135G/C polymorphism located in the 5' untranslated region seems to be of functional relevance.…”
Section: Discussionmentioning
confidence: 93%
“…Different meta-analysis and studies on RAD51 have earlier shown an association of this polymorphism with an elevated breast cancer risk (Cole et al, 2011;Falvo et al, 2011;Gao et al, 2011;Hosseini et al, 2012). The RAD51 135G/C polymorphism located in the 5' untranslated region seems to be of functional relevance.…”
Section: Discussionmentioning
confidence: 93%
“…We found that the SNP in the RAD 51 gene GC genotype (OR 1.73, 95% CI 1.14–2.62, p  = 0.02) may be an important predictive determinant for UC. Hosseini et al , (2013) [29] also demonstrated that there was a significant association of breast cancer risk with RAD 51 polymorphism. Wang et al , (2001) [30] identified a RAD 51 SNP that may be associated with an increased risk of breast cancer and a lower risk of ovarian cancer.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, interest in genetic susceptibility to cancers has led to growing attention to the study of polymorphisms of genes involved in tumourigenesis [17][18][19][20][21]. Functional polymorphisms in genes encoding onecarbon metabolism enzymes, methylenetetrahydrofolate reductase (MTHFR C677T), methionine synthase (MTR A2756G), methionine synthase reductase (MTRR A66G) and thymidylate synthase (TS), influence folate metabolism, but epidemiological studies have yielded inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%